Meningkatkan Kemampuan Berpikir Kritis Peserta Didik MI Melalui Model Pembelajaran Inkuiri - Baharudin, Baharudin; Fiteriani, Ida; Munafiroh, Verawati; Susilawati, Susilawati (AR-RIAYAH: Jurnal Pendidikan Dasar, 2024)
The study of improving critical thinking skills has garnered attention worldwide, including in Indonesia, amidst the developments and advancements of the 21st century. The enhancement of critical thinking skills among students is often overlooked by teachers in the classroom. This research aims to analyze students' critical thinking abilities using the inquiry learning model. The research design employed in this study is quantitative research with a quasi-experimental design. The sample consisted of 61 fifth-grade students from an Islamic elementary school. The findings indicate a significant comparison of students' critical thinking abilities using the inquiry learning model, as revealed by the t-test results. The implications of this research can serve as a reference for taking further action to address issues related to improving critical thinking skills and fostering innovative learning approaches. This study is expected to be utilized by educators as a reference to enhance students' thinking abilities.